Speech motor brain regions are differentially recruited during perception of native and foreign-accented phonemes for first and second language listeners - Callan, Daniel; Callan, Akiko; Jones, Jeffery A. (Frontiers in Neuroscience, 2014)
Brain imaging studies indicate that speech motor areas are recruited for auditory speech perception, especially when intelligibility is low due to environmental noise or when speech is accented. The purpose of the present study was to determine the relative contribution of brain regions to the processing of speech containing phonetic categories from one’s own language, speech with accented samples of one’s native phonetic categories, and speech with unfamiliar phonetic categories. To that end, native English and Japanese speakers identified the speech sounds /r/ and /l/ that were produced by native English speakers (unaccented) and Japanese speakers (foreign-accented) while functional magnetic resonance imaging measured their brain activity. For native English speakers, the Japanese accented speech was more difficult to categorize than the unaccented English speech. In contrast, Japanese speakers have difficulty distinguishing between /r/ and /l/, so both the Japanese accented and English unaccented speech were difficult to categorize. Brain regions involved with listening to foreign-accented productions of a first language included primarily the right cerebellum, left ventral inferior premotor cortex PMvi, and Broca’s area. Brain regions most involved with listening to a second-language phonetic contrast (foreign-accented and unaccented productions) also included the left PMvi and the right cerebellum. Additionally, increased activity was observed in the right PMvi, the left and right ventral superior premotor cortex PMvs, and the left cerebellum. These results support a role for speech motor regions during the perception of foreign-accented native speech and for perception of difficult second-language phonetic contrasts.